2019
DOI: 10.11613/bm.2019.030706
|View full text |Cite
|
Sign up to set email alerts
|

Rapid serum tube technology overcomes problems associated with use of anticoagulants

Abstract: Introduction: Failure to obtain complete blood clotting in serum is a common laboratory problem. Our aim was to determine whether snake prothrombin activators are effective in clotting blood and producing quality serum for analyte measurement in anticoagulated patients. Materials and methods: Whole blood clotting was studied in a total of 64 blood samples (41 controls, 20 Warfarin patients, 3 anticoagulated patients using snake venom prothrombin activator (OsPA)) with plain tubes. Coagulation was analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 28 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…In initial experiments, a simple tube mixing clotting assay was used with plain collection tubes (Greiner Bio One, Kremsmünster, Austria) pre-coated with hydrophilic surfactant (Dow Corning, Midland, MI, United States). This has been previously reported and shown to be a reliable estimate of blood clotting times (Zhao et al, 2019). To each tube, 20 µL of the 10-fold concentrated cell conditioned medium, 50 µL of 1 M CaCl 2 and 3.95 mL of citrated normal whole blood were added.…”
Section: Blood Clotting Assaysmentioning
confidence: 99%
“…In initial experiments, a simple tube mixing clotting assay was used with plain collection tubes (Greiner Bio One, Kremsmünster, Austria) pre-coated with hydrophilic surfactant (Dow Corning, Midland, MI, United States). This has been previously reported and shown to be a reliable estimate of blood clotting times (Zhao et al, 2019). To each tube, 20 µL of the 10-fold concentrated cell conditioned medium, 50 µL of 1 M CaCl 2 and 3.95 mL of citrated normal whole blood were added.…”
Section: Blood Clotting Assaysmentioning
confidence: 99%
“…These PAs can clot blood with high efficiency, without being subject to the regulation observed with human Factors X and V [ 1 , 2 ]. Snake prothrombin activator sources include those from Oxyuranus scutellatus (Australian Coastal Taipan (OsPA) that from Pseudonaja textilis (Australian common brown snake) (PtPA) and ecarin from Echis carinatus [ 3 , 4 , 5 , 6 , 7 ]. Recently, we employed OsPA for the rapid preparation of consistently high-quality serum using blood from both normal individuals and anticoagulated patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Snake prothrombin activator sources include those from Oxyuranus scutellatus (Australian Coastal Taipan (OsPA) that from Pseudonaja textilis (Australian common brown snake) (PtPA) and ecarin from Echis carinatus [ 3 , 4 , 5 , 6 , 7 ]. Recently, we employed OsPA for the rapid preparation of consistently high-quality serum using blood from both normal individuals and anticoagulated patients [ 5 , 6 ]. We demonstrated that OSPA converted prothrombin to thrombin in the blood sample, generating [ 5 , 6 ] a bolus of thrombin significantly greater than the amount used in commercially available thrombin tubes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations